2002
DOI: 10.14411/eje.2002.051
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the ability to synthesize juvenile hormone in vitro by corpora allata from the Eri silkworm, Samia cynthia ricini (Lepidoptera: Saturniidae)

Abstract: Abstract. A radiochemical assay (RCA) has been used for the measurement ofjuvenile hormone (JH) synthesis in vitro by corpora allata (CA) from the Eri silkworm, Samia cynthia ricini. Using CA from newly emerged female adults for the bioassay, the most suitable incubation conditions were determined. A high rate of JH synthesis was found in medium TC199 at pH 6.5, 30°C and 4 mM Ca2+. The time course of JH synthesis showed a steady decrease during the first 6 hours of incubation.Under optimal incubation condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Under optimal incubation conditions, two peaks of JH synthesis were found on day 1 of the fifth-instar larvae and at the time of adult emergence. A significant sexual dimorphism of JH synthesis was observed during the period of adult emergence (Li et al, 2002a). This study has demonstrated that Samcri-JHAMT, but not -HMGR, is the key regulatory enzyme for JH synthesis in the Eri silkworm, at both molecular and enzymatic levels.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Under optimal incubation conditions, two peaks of JH synthesis were found on day 1 of the fifth-instar larvae and at the time of adult emergence. A significant sexual dimorphism of JH synthesis was observed during the period of adult emergence (Li et al, 2002a). This study has demonstrated that Samcri-JHAMT, but not -HMGR, is the key regulatory enzyme for JH synthesis in the Eri silkworm, at both molecular and enzymatic levels.…”
Section: Discussionmentioning
confidence: 63%
“…Second, JHAMT was regulated at the transcriptional level. During the period of adult emergence, the acute change of Samcri-JHAMT activity exactly matched that of JH synthesis (Li et al 2002a). Although Samcri-JHAMT mRNA level shared a similar pattern to that of Samcri-JHAMT activity, the former peak was a few hours earlier than the later one suggesting a short delay of translational and/or posttranslational processes.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In Samia cynthia ricini, developmental changes in the CA ability to synthesize JH was investigated in vitro using a modified radiochemical assay (RCA) (Li et al, 2002a). Both AT and AST activities were detected in the brain extracts, and Manse-AT and -AST were shown to stimulate and inhibit, respectively, JH synthesis in isolated CA (Li et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%